국산 참다래 골드 신품종 도입농가의 경영성과 및 경영효율성 분석 - 박재형(Jae Hyoung Park), 채용우(Yong Woo Chae), 박주섭(Joo Sub Park) (농촌지도와 개발, 2016)
The purpose of this study is to analyze the farms growing domestic kiwi fruit 'Gold' on their management performance and efficiency in order to reduce the risks involved with introducing new kind of crops for growing, and suggest improvements. First, the result of analysis showed that domestic kiwi fruit 'Gold' growers' income were higher than the average growers due to the fruit's high unit price and productivity. Second, the analysis of management efficiency resulted in scale efficiency having greater impact on inefficiency rather than pure technical efficiency. As for the analysis of technical efficiency, the depreciation costs of agricultural facilities had the greatest influence on its inefficiency. Third, inefficient farms put in excessive inputs across the board, while labor costs(self labor cost + hired labor cost) were the largest factor of optimal inputs according to the models of technical efficiency and pure technical efficiency. Fourth, because of greater reliance on mechanical tools from rising labor costs, there's a need for individual farms to avoid buying farming equipments and instead share the equipments of nearby farms and agricultural cooperatives, or start renting agricultural machines from companies.